Host-endosymbiont co-evolution shaped chloroplast translational regulation. Issue 3 (3rd July 2019) - De Marchis, Francesca; Pompa, Andrea; Ballottari, Matteo; Bellucci, Michele
ABSTRACT: The interaction between organisms and their environment generates evolutionary forces able to modify a living species. The process of gene expression, from the transcription of information encoded in a gene to the synthesis of a functional polypeptide, largely relies on evolution, which plays a significant role in determining the factors that control and regulate gene expression. Nowadays, chloroplasts are the result of a complex evolutionary history, elicited by the intracellular cohabitation of an ancient photosynthetic cyanobacterium inside a mitochondriate eukaryotic cell. In this paper, we try to describe the recent investigations on mechanisms that regulate chloroplast translation, both in Chlamydomonas reinhardtii and in land plants. After a general description of plastid translational machinery, ribosome structure with related proteins and nuclear-encoded proteins regulating plastid translation in these organisms, we focus on specific examples of chloroplast translation regulation in the green lineage. In the end, we provide a comparison between plastid translation regulation in green algae and land plants, showing that in both cases chloroplast gene expression is prevalently regulated at post-transcriptional and translational level, although with different strategies.